2021
DOI: 10.3390/ma14071713
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Dentin Graft: A Review on Its Osteoinductivity and Antigenicity

Abstract: Studies on allogeneic demineralized dentin matrix (Allo-DDM) implantation in the 1960s and 1970s provided the most reliable preclinical evidence of bone formation and antigenicity in an extraosseous site. Recently, applications of Allo-DDM at skeletal sites were studied, and have provided reliable evidence of bone-forming capacity and negligible antigenicity. However, the osteoinductivity and antigenicity properties of Allo-DDM in extraskeletal sites have not yet been investigated due to the lack of follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…It suggested that only the outer surface of HTDM has the conditions to form neo‐cementum, including scaffold structure, material microenvironment, et al, and the formation of neo‐cementum was directional too, consistent with the development of cementum and the secretion of extracellular matrix on the outer surface of HTDM in vitro. This was consistent with lots of literatures of demineralized dentin matrix, which have shown that demineralized dentin matrix has strong osteogenic induction ability, and even freeze‐dried or inactivated dentin matrix can induce osteogenesis 55‐57 . The osteogenic induction ability of demineralized dentin matrix may be independent of the active proteins in dentin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It suggested that only the outer surface of HTDM has the conditions to form neo‐cementum, including scaffold structure, material microenvironment, et al, and the formation of neo‐cementum was directional too, consistent with the development of cementum and the secretion of extracellular matrix on the outer surface of HTDM in vitro. This was consistent with lots of literatures of demineralized dentin matrix, which have shown that demineralized dentin matrix has strong osteogenic induction ability, and even freeze‐dried or inactivated dentin matrix can induce osteogenesis 55‐57 . The osteogenic induction ability of demineralized dentin matrix may be independent of the active proteins in dentin.…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with lots of literatures of demineralized dentin matrix, which have shown that demineralized dentin matrix has strong osteogenic induction ability, and even freeze-dried or inactivated dentin matrix can induce osteogenesis. [55][56][57] The osteogenic induction ability of demineralized dentin matrix may be independent of the active proteins in dentin. On the other hand, there was no neo-dentin or mineralized tissue formation on the outer surface of LTDM, and there were masses of cells and some collagen fibers, which were tightly bound to the outer surface of LTDM.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the topic of tooth root grafts and specifically allografts has been extensively investigated in the 1960s–1970s, and the topic regained interest in recent years 28 . However, ATR in the present study is quite different from the demineralized dentin matrix (DDM) in previous studies, although they look similar.…”
Section: Discussionmentioning
confidence: 47%
“…Bovine dentine is easy to obtain, morphologically similar to human dentine, and possesses protein derivatives to support bone growth, namely BMP and TGF-β. 1,5,9,10 Performance measurement of mitochondrial dehydrogenase, also known as 3-(4,5-dimethyl-2-thiazolyl test) −2,5-diphenyl-2H-tetrazolium bromide (methyl thiazolyl tetrazolium; MTT), is a rapid assessment of cell proliferation and a colorimetric cytotoxicity test that can be lead into the cell metabolism or cell function measurement. The 446 basic idea is that the tetrazole ring would be cut by mitochondrial dehydrogenase in the cytochrome b and c sites of live cells.…”
Section: Discussionmentioning
confidence: 99%